Gonad Sex Differentiation of Anguilla anguilla by Sex Steroids - COLOMBO, Giuseppe; GRANDI, Gilberto (Internationale Revue der gesamten Hydrobiologie und Hydrographie, 1990)
Anguilla anguilla elvers, reared in warm fresh water, were treated with 17 alfa-methyltestosterone (MT)' and with 17 alfa-ethynilestradiol (EE), administered with. a commerciaI diet. A very low proportion of untrented elvers developed as females. A very high proportion of the EE treated elvers developed as females and the gonads differentiated .as ovaries at an earlier growth stage. Among the MT treated elvers, in a very low proportion of eels the gonads deve1oped as ovaries, most into a undifferentiated testis-like gonad and some with abnormal histological features.